Integrating sustainable development into their marketing strategy: practices of Lebanese agri-food industries - Davidavičienė, Vida; Abou Fayad, Cendrella; Gergess, Marc (Business: Theory and Practice, 2024)
Amidst technological growth and its environmental implications, there’s a global push for sustainable development using ethical methods that benefit both the planet and humanity. This underscores a rising corporate trend towards sustainability. Adopting this approach requires fresh methods and technologies to influence behavior changes. Consequently, marketing, when aligned with sustainability principles, becomes a pivotal tool for businesses transitioning to sustainable practices. The food industry, like other sectors, is not exempt from these considerations. This article focuses on examining how food industries in Lebanon are incorporating sustainable development principles into their marketing strategies. By studying their approaches, we aim to identify the level of integration of sustainability within the marketing practices of these industries, identify gaps, and to bring the future scientific research directions in marketing management. Thus, this research is conducted following the post-positivist paradigm and following a hypothetical-deductive approach. Hence the qualitative research and expert evaluation used to collect data due to its applicability to the context of the study. The target respondents are managers of the agri-food industries in order to measure the good practices of sustainable development of these industries and their Marketing strategy based on the 4Ps. Lebanon’s distinct challenges, from environmental to economic, call for specialized solutions. Achieving sustainability involves grasping local nuances, engaging stakeholders, and connecting different sectors. Sustainable marketing emphasizes local products and community ties, offering potential for significant change. The study indicates agri-food businesses mainly focus on environmental and economic elements. Yet, the research faced hurdles, like the pandemic, highlighting the need for context-awareness.